To study the effect of hydroxyurea on transcranial doppler in patients with sickle cell anemia - Phuljhele, Sharja; Pandey, Prankur; Banjare, Rajesh (Pediatric Review: International Journal of Pediatric Research, 2020)
Background: The estimated rate of prevalence of SCD in the population of Chhattisgarh is about 10 to 15% of which about 1 to 1.27% are likely to be sufferers and the rest carriers.The frequency of stroke in SCD is estimated at 0.61 per 100 patients per year. TCD is a valuable screening test in many clinical conditions such as SCD, to identify the patients at risk of stroke. An abnormally high blood speed is an indicator of a narrowed cerebral blood vessel and/or increased blood volume and a warning marker of high risk for stroke. Methods: This was a prospective comparative cross-sectional observational hospital based study, conducted over a period of 17 months (July 2016 to November 2017) in the Department Of Pediatrics and Radiodiagnosis, Dr. B.R.A.M.H, Raipur (C.G.).Children between 2 to 14 years diagnosed as SCD SS who were receiving long term (>6months) HU(hydroxyurea) treatment (cases) – HU group, and those who had never received this treatment (control) – HU naïve group, were enrolled. Results: The total number of children enrolled in the present study was 120, out of which 40 were cases and 80 were controls. The mean blood flow velocity of cases was significantly lower than controls. Among cases and controls maximum mean blood flow velocity was found in Left MCA followed by Right MCA. In addition to this, it was also found that there was no significant interhemispheric difference in both group. (p-value more than 0.05).There were significant associations between blood flow of Right andLeft Side of MCA, ACA and ophthalmic arteries among cases. Conclusion: The mean blood flow velocity in the HU group and HU naïve group was within the normal range (<170cm/sec), as per STOP criteria. The mean blood flow velocity in patients who were on the HU group was found to be significantly lower than the HU naïve group.